A SoC-Based Programmable Portable Ultrasound Scanning System for Point-of-Care Applications and Clinical Research Activities - Bharath, R.; Santhosh Reddy, D.; Rajalakshmi, P. (SN computer science, 2022)
In this paper, we propose a programmable SoC-based hardware framework that can be used for developing a complete clinical portable ultrasound scanning (PUS) system for remote healthcare, point-of-care diagnostics and clinical research activities. The system is developed for 16 channel data acquisition and is provided with additional external interfaces like Ethernet, RS-232, HDMI, VGA and USB ports enabling the system for more reliable diagnostics in remote healthcare settings. To reduce the size of the ultrasound scanning system, the front-end signal processing hardware along with the external interfaces are integrated on an eight layered printed circuit board (PCB). The front-end processing, which includes analog signal conditioning and transmit beamforming are implemented on dedicated hardware, while the mid-end and back-end processing algorithms are implemented on the FPGA processor. The controlling and coordination between the entire processing modules are done using an onboard ARM processor. The developed PUS serves three main purposes: (1) it can be used to acquire RF data at different instances of the signal processing modules that can be used for testing new algorithms and developing computer-aided diagnostics, (2) provided with JTAG and UART ports that can be used for testing and debugging the algorithms while up-gradation, and (3) the proposed system can be interfaced with a smart phone to access the scanned data from the ultrasound board for display. The developed PUS have a dimension 235 mm × 205 mm and weigh approximately 450 g.